Technical figure skating - Anderson, K.
The purpose of this page is to provide multimedia resources to give a better understanding of the technical aspects of figure skating. This is accomplished in several ways. The first way is by providing AVI movie clips and multi frame GIF images of all the major jumps, spins, jump spins, and extras. The second way is by providing links to other sources of technical information, such as books, magazines, and videos. There is a page dedicated to a discussion on skating equipment and where to find it on the net. The last way is by sharing my own observations and insights based on many years of skating experience. My main motivation for putting the Technical Figure Skating page together is to share some of the same digitized video clips that I use to improve my own skating. If you know how to use a computer and how to apply what you see to your own skating, then they are as valuable as having a top notch coach. And, unlike a real coach, they don't get upset when you dump them for a new set of video clips from Lake Arrowhead.